HALAL PRODUCT AS A COMPETITIVE ADVANTAGE: THE ROLE OF HUMAN RESOURCES AND GREEN TRANSFORMATIONAL LEADERSHIP - Hasriani Hasriani; Sirajuddin Sirajuddin; Rahmawati Rahmawati (Journal of Islamic Economics and Finance, 2025)
In the era of globalization, halal products have evolved beyond mere compliance with Islamic law to become global symbols of quality, ethics, and sustainability. The rapid growth of the halal market, particularly in food, cosmetics, and pharmaceuticals, offers strategic opportunities for companies to leverage halal as a source of sustainable competitive advantage. However, the main challenges in the halal industry lie not only in certification but also in the organizational capacity to manage human resources (HR) and foster leadership that integrates sustainability values. This Study explores how HR and green transformational leadership contribute to competitive advantage in Indonesia’s halal industry through a qualitative approach using multiple case studies of three certified halal companies. The findings reveal that strengthening halal- and ethics-based HR competencies, along with visionary, participatory, and environmentally conscious leadership, are critical in driving innovation and operational efficiency aligned with maqasid syariah principles. Theoretically, this study expands the integration of the resource-based view (RBV) and natural resource-based view (NRBV) within the halal management context. Practical implications highlight the need for reformulating HR policies and leadership development programs that embed halal principles and sustainability. This research addresses conceptual and practical gaps by offering a strategic and holistic perspective on halal product management in achieving long-term competitiveness.